Transcriptomic and experimental evidence confirm the potential of disulfidptosis-related signature for the early diagnosis and treatment of liver cirrhosis - Yiqian Liu; Ruixin Zhang; Xiaojie Sun; Wei Cui; Lixin Liu (PLoS ONE, 2025)
Cirrhosis is a common endpoint in various chronic liver diseases, and often causes hepatocellular carcinoma. Studies have revealed the significant role of disulfidptosis in the occurrence and development of hepatocellular carcinoma; however, our understanding of this role is limited. Therefore, we aimed to identify potential disulfidptosis-related biomarkers for cirrhosis. We obtained the gene expression data of patients with cirrhosis from the Gene Expression Omnibus (GEO) database. Subsequently, weighted gene co-expression network analysis was performed, and the “limma” package was used to screen for differentially expressed genes (DEGs) associated with disulfidptosis. Significantly altered biological pathways were identified using Gene Ontology (GO), Kyoto Encyclopedia of Genes and Genomes (KEGG), Gene Set Enrichment Analysis (GSEA), and Gene Set Variation Analysis (GSVA). We constructed protein–protein interaction (PPI) networks using GeneMANIA and generated receiver operating characteristic (ROC) curves to identify hub-shared genes. Additionally, we assessed the distribution of immune cell populations in cirrhotic and control specimens using single-sample GSEA (ssGSEA) and explored their relationship with hub genes. Six hub genes ( CXCL12, COL1A1, CXCR4, COL1A2, CCR7, and CXCL8 ) were closely associated with disulfidptosis-related DEGs. Further immunohistochemical experiments confirmed the potential of CCR7, CXCL12, CXCR4, and CXCL8 as novel diagnostic biomarkers and suggested their potential as new therapeutic targets. These genes mainly promote the development of liver cirrhosis through the oxidative metabolism and cytokine pathways. Furthermore, we observed positive correlations among 23 of the 28 types of immune cells. This study highlights the potential utility of immune cell infiltration and efficient disulfidptosis-related early diagnostic biomarkers in cirrhosis, and highlights its strong useful as a therapeutic target, offering potential clinical application value.